Sociocultural mechanisms of Oralmans’ adaptation in the contemporary Kazakhstani society - Baudiyarova k., Sapatayev S., Kalysh A., Kassymova D., Isayeva A., Meirmanova G., (Opción, 2019)
The objective of the article is to make preliminary generalizations for further research on repatriates’ adaptation models via comparative qualitative research methods. As a result, the case of Kazakhs coming from Uzbekistan is interesting as it provides an opportunity to look at how Kazakh practices survived in Uzbek environment and now serve the purpose to breed true Kazakhness on Kazakh soil. In conclusion, the employment of Mahalla model by the Ak Ordasy Corporation was necessitated by the limited time and space specifics and the nature of the population under their responsibility.